2009
DOI: 10.1210/en.2008-1639
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Effects of Adiponectin on Bone

Abstract: Fat mass impacts on both bone turnover and bone density and is a critical risk factor for osteoporotic fractures. Adipocyte-derived hormones may contribute to this relationship, and adiponectin is a principal circulating adipokine. However, its effects on bone remain unclear. We have, therefore, investigated the direct effects of adiponectin on primary cultures of osteoblastic and osteoclastic cells in vitro and determined its integrated effects in vivo by characterizing the bone phenotype of adiponectin-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(99 citation statements)
references
References 55 publications
3
95
0
1
Order By: Relevance
“…The hormonal regulation of AMPK activation in bone has not been extensively studied. Adiponectin, which increases osteoblast proliferation and differentiation (Oshima et al 2005) but has controversial effect on bone mass in vivo (Williams et al 2009), can stimulate AMPK phosphorylation in MC3T3-E1 osteoblastic cells (Kanazawa et al 2007). We showed that AMPK phosphorylation and activity in ROS17/2.8 cells was stimulated by ghrelin (Shah et al 2010), a hormone known to stimulate osteoblast differentiation and function (Maccarinelli et al 2005, van der Velde et al 2008.…”
Section: Subunit Expression and Ampk Regulation In Bone Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…The hormonal regulation of AMPK activation in bone has not been extensively studied. Adiponectin, which increases osteoblast proliferation and differentiation (Oshima et al 2005) but has controversial effect on bone mass in vivo (Williams et al 2009), can stimulate AMPK phosphorylation in MC3T3-E1 osteoblastic cells (Kanazawa et al 2007). We showed that AMPK phosphorylation and activity in ROS17/2.8 cells was stimulated by ghrelin (Shah et al 2010), a hormone known to stimulate osteoblast differentiation and function (Maccarinelli et al 2005, van der Velde et al 2008.…”
Section: Subunit Expression and Ampk Regulation In Bone Cellsmentioning
confidence: 73%
“…The bone loss in age-related osteoporosis is associated with more adipogenesis and less bone formation (Pei & Tontonoz 2004). Second, there are direct actions on bone of hormones produced by adipocytes, such as adiponectin and leptin, as well as of hormones released by the pancreas, gut and pituitary (Cornish et al 1996, Maccarinelli et al 2005, Williams et al 2009). In addition, the recent discovery that leptin can inhibit bone formation through hypothalamic and sympathetic nervous system relays , Takeda et al 2002, Elefteriou et al 2005 has demonstrated that bone can not only be directly affected by hormones which have receptors on bone cells, but can also be influenced by the same hormones acting on receptors in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies also found that this adipokine promotes osteoblastogenesis but negatively regulates adipogenesis [116][117][118]. However, in vivo studies with adiponectin-deficient mice showed agedependent increase in trabecula volume and number suggesting that adiponectin has both direct and indirect effects on bone in vivo, and is also a likely contributor to bone mass [118]. The role of other adipokines in MSC differentiation is less clear, however, recent findings suggest that most of these adipokines may play a role in regulating bone metabolism and remodeling [98].…”
Section: Excessive Adipose Tissuementioning
confidence: 95%
“…Adiponectin is another adipose secreted adipokine with critical roles in glucose metabolism and energy homeostasis [115]. In vitro studies also found that this adipokine promotes osteoblastogenesis but negatively regulates adipogenesis [116][117][118]. However, in vivo studies with adiponectin-deficient mice showed agedependent increase in trabecula volume and number suggesting that adiponectin has both direct and indirect effects on bone in vivo, and is also a likely contributor to bone mass [118].…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…Studies in vitro and in vivo have yielded contradictory results regarding the effects of Adipoq on bone cell function. Adipoq has been shown to either stimulate or suppress osteogenesis in vitro (Lee et al, 2009;Shinoda et al, 2006;Williams et al, 2009) and the results from in vivo studies using Adipoq knockout or overexpressing mice are also conflicting (Ealey et al, 2008;Oshima et al, 2005;Shinoda et al, 2006;Williams et al, 2009). This indicates that Adipoq could additionally contribute to the bone phenotype by suppressing bone forming activity in osteoblasts in an autocrine fashion.…”
Section: (N56) (Gh) Glucose Tolerance (Gtt) and Insulin Tolerance (mentioning
confidence: 99%